Identifikasi Kapasitas Tampang Minimum dan Stabilitas Mulut Muara Sungai Siak Propinsi Riau - Sujatmoko, Bambang; Pratama, Rizki; Hendri, Andy; Rinaldi, Rinaldi (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
Changes in river mouth section capacity caused by instability of river mouth stability would influence flow conditions in upstream estuaries, as impacted by unsmooth drainage of river flow. Section river capacity and mouth river stability of Siak River would be evaluated by the output of tidal prism at the estuary. The tidal prism was predicted by Hecras software. Input data for hydrodynamic simulation consisted of river geometric data, river bed condition, and boundary condition (discharge and water level). The maximum daily rainfall data and Siak’s catchment parameter could predict flood discharge. Longshore sediment transport netto data could be calculated using wave depth data, wave velocity data and direction of wave around the mouth river. The results of the tidal prism calculation show that the existing cross-sectional area of the mouth of the Siak River estuary can only drain the volume of water due to discharge and tides in the 2-year return period (Amin = 3,115 m2 < A ada = 3,225 m2), while for discharge with other return periods, the capacity of the cross-section river is not sufficient. The excess discharge will flow upstream as a backwater. Siak River mouth stability is still relatively good and stable, with a stability number (S) of more than 388,0 (requirement: S > 150). The start of the backwater effect at KM+220 (60 km from the mouth of the river) caused a significant change in water level (0.94 m) due to the damming of the flow caused by the influence of tides and the bifurcation node of the river (delta).